Fetal loss and malformations in the MONEAD study of pregnant women with epilepsy. (7th April 2020) - Meador, Kimford J.; Pennell, Page B.; May, Ryan C.; Van Marter, Linda; McElrath, Thomas F.; Brown, Carrie; Gerard, Elizabeth; Kalayjian, Laura; Gedzelman, Evan; Penovich, Patricia; Cavitt, Jennifer; French, Jacqueline; et al.
Abstract : Objective: To examine occurrence of severe adverse fetal outcomes (SAO), including fetal loss and major congenital malformations (MCMs), in pregnant women with epilepsy (PWWE) vs healthy pregnant women (HPW). Methods: The Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs (MONEAD) study is an NIH-funded, prospective, observational, multicenter investigation of pregnancy outcomes for both mother and child, which enrolled women December 2012 through January 2016. Results: The 351 PWWE had 365 conceptions, and 105 HPW had 109 conceptions. SAOs occurred more often in PWWE (7.9%) vs HPW (1.9%) ( p = 0.025) with odds ratio (OR) 4.45 (95% confidence intervals [CI] 1.04–19.01). There were no significant differences for fetal loss (2.8% vs 0%, p = 0.126) or MCMs (5.2% vs 1.9%, p = 0.185; OR 2.86, 95% CI 0.65–12.53) individually. No fetal losses in PWWE appeared to be related to acute seizures. Outcomes were not affected by periconceptional folate, unplanned/unwanted pregnancies, prior maternal pregnancy history, or antiepileptic drug (AED) blood levels, except for an AED level effect for fetal loss that appeared to be due to polytherapy. Combined maternal or paternal family history of MCM was marginally associated with increased SAOs ( p = 0.046). Conclusions: The findings provide additional information on risks of SAOs in PWWE, assessing effects of both AED levels and periconceptional folate. Group differences in average enrollment gestational age could have affected fetal loss results. Analyses are limited by small sample sizes as the MONEAD study was not powered for these secondary outcomes. The large majority of pregnancies in women with epilepsy do not have SOAs.